Evaluation of the protective effect of quercetin and luteolin against ciprofloxacin- and chloramphenicol-induced oxidative stress in blood cells and their impact on the microbiological activity - Bustos, Pamela Soledad; Echeverría, Javier; Páez, Paulina Laura; Ortega, María Gabriela (Frontiers in Pharmacology, 2025)
BackgroundThe induction of oxidative stress (OS) in host cells by antibiotics (ATBs) such as ciprofloxacin (CIP) and chloramphenicol (CMP) is associated with their side effects. Flavonoids such as quercetin (Q) and luteolin (LT) could counteract the harmful effects related to OS induced by ATBs.PurposeThe purpose of this research was to investigate the in vitro effect of CIP and CMP alone and plus Q and LT on ROS production, endogenous antioxidant defenses [superoxide dismutase (SOD) and catalase (CAT)], and protein oxidation (PO) on human leukocytes, evaluating the protective action of Q and LT on the toxicological effects of CIP and CMP.Materials and methodsQ and LT were isolated from F. bidentis leaves and S. strombulifera fruits, respectively, and identified by spectroscopic and chromatographic techniques. Cell viability was assessed by the exclusion of the dye trypan blue, and intracellular reactive oxygen species (ROS) were detected by fluorescence using the H2-DCFDA assay. Riboflavin/methionine/NBT and H2O2/dichromate/acetic acid reagents, respectively determined SOD and CAT activities. The advanced oxidation protein products assay was used to assess PO. Q and LT interactions with CIP and CMP were evaluated by checkerboard assay in S. aureus and E. coli.Results and discussionBoth ATBs were capable of increasing ROS production in polymorphonuclear cells, and Q and LT were more effective in inhibiting it than vitamin C. Regarding SOD and CAT activity, CIP and CMP altered their activity. Regardless of an increase in enzymatic activity, as in the case of CIP, or a decrease in antioxidant systems, as in the case of CMP, both flavonoids restore enzymatic activity to similar values as those of control cells. Concerning the PO increase observed by CIP and CMP, both Q and LT can prevent it. Finally, the association of flavonoids and ATBs on antimicrobial activity in S. aureus and E. coli shows antibacterial synergism between LT and both ATBs in the S. aureus ATCC strain, thereby enhancing antibacterial activity.ConclusionThese in vitro findings stimulate in vivo research to assess if simultaneous administration of LT/Q with CIP/CMP could be a therapeutic option capable of protecting the host against antibiotic-induced OS in systemic circulation, enhancing antibacterial activity in case of LT. More studies are necessary in order to contribute to this hypothesis.